Improving Economic Firms Performance through Co-opetition Strategy - Morteza Soltani; Seyyed Mohammad Bagher Jafari; Razieh Binandeh (مطالعات مدیریت راهبردی, 2016)
Studies show that in the today global business environment, the pace of change and uncertainty and competition is growing up. In this environment, those competitors will have a better performance that work together on parts of their value chain. Cooperation between competing companies that so called co-opetition is one of the new business strategies for dealing with the environment uncertainty. This study sought to examine the impact of co-opetition strategy on innovation performance and market performance of companies by considering uncertainty in the market, the intensity of competition and network externalities as moderating variables. This is an applied study, using quantitative approach to test the developed hypotheses. The study population consists of Iranian companies operating in the information technology industry (IT). Data were collected from 180 companies. The hypotheses were tested using structural equation modeling. The results showed that co-opetition has significant positive impact on innovation performance and the performance of the market. Meanwhile, the intensity of competition and the uncertainty in market moderate the relationship between the co-opetition and innovation performance.